Are the Requirements for Teacher’s Competence set by University Administration and Students Similar? - Razmaitė, Danguolė; Dagys, Džeraldas (Pedagogika, 2014)
As the educational paradigm undergoes changes, new challenges for performance and competence of higher education institution teachers arise. The article deals with the Requirements for teacher’s competence set by university administration and students, and whether these requirements are similar. In the beginning, definitions of teacher’s competence dealt with in scientists’ papers are reviewed, the structure of teacher’s competence is discussed. The article explores the requirements for teacher’s competence set by university administration and students. The research carried out shows that nevertheless there is a divide between requirements for teachers’ competence set by university students and university administration. It should be noted that university administration pose requirements which are regulated on the national level of the Republic of Lithuania, i.e. provisions of the Law on Higher Education and Studies of the Republic of Lithuania; whereas the definitions of competences investigated by scientists remain as a theoretical construct, a scientific outcome. The requirements set by students include these teachers’ competences (pedagogical, meta-learning, technical, etc.) which interact with the efficiency and quality of the teaching process.